Gain enhancement of microstrip patch antenna using low loss negative refractive index metamaterial superstrate - Ng, C. H.; Devi, K. K. A.; Chakrabarty, C .K.; Norashidah, Md. Din; Kwong, C.F. (Universiti Teknikal Malaysia Melaka, 2017)
A novel microstrip patch antenna (MPA) based on planar negative refractive-index metamaterial is proposed. It is demonstrated that the proposed nested split ring resonator (SRR) structure metamaterial yields an effective refractive index that equal to negative value over the frequency range of 770 MHz to 1070 MHz The negative refractive index structure is applied as a superstrate to a C-shaped microstrip patch antenna. The simulation results show that the gain is effectively improved by 2.64 dB (119 %) after the incorporation of negative refractive index metamaterial superstrate. The results illustrated that the gain of the proposed antenna is enhanced over the desired frequency band 935 MHz to 960 MHz. The air gap between the antenna and superstrate was also studied by applying the theory of Fabry-Perot (F-P) resonant cavity to obtain the optimum air gap of 55 mm to achieve the maximum gain.